Analisis Dampak Implementasi Pelatihan Soft Skill Identifikasi Potensi Dasar mengelola Diri - Astuty, Isthofaina (Universitas Muhammadiyah Yogyakarta, 2010)
This reaserch is intended to identify the self management level (personality) of UMY boardinghouse resident. The number of reaserch is 96 (52 female and 43 male). The data were analized by Mean Analysis and Independent Sample T-test.The mean analysis result indicate that the self management of the student is the same lavel. Independent sample T-test indicate that female and male resident have the sampe level of self management. At the other side, the self management level is difference depend on the faculty.